Reduced Activity in an Inpatient Liaison Psychiatry Service During the First Wave of the COVID-19 Pandemic: Comparison With 2019 Data and Characterization of the SARS-CoV-2 Positive Cohort - Butler, Matthew; Delvi, Afraa; Mujic, Fedza; Broad, Sophie; Pauli, Lucy; Pollak, Thomas A.; Gibbs, Soraya; Fai Lam, Chun Chiang Sin; Calcia, Marilia A.; Posporelis, Sotirios (Frontiers in Psychiatry, 2021)
Background The COVID-19 pandemic led to changes in the way that healthcare was accessed and delivered, particularly during the peak lockdown period. There have been suggestions that COVID-19 will lead to acute neuropsychiatric manifestations in the acute phase, with variable effect on mental health in the longer term. Despite this, there are limited data on the direct effects of the COVID-19 pandemic on psychiatric care. Methods In this retrospective study we present a descriptive summary of referrals to an inpatient psychiatric liaison department in a large acute teaching hospital during the exponential phase of the pandemic in the United Kingdom, and compare this to the same period in 2019. Results We saw a 40.3% reduction in the number of referrals in 2020, with an increase in the proportion of referrals for delirium and psychosis. One third (28%) of the referred patients tested positive for COVID-19 at some point during their admission, with 39.7% of these presenting with delirium as a consequence of their COVID-19 illness. Conclusion Our data indicate decreased clinical activity for our service during the peak of the current pandemic, the reasons for which are likely multifactorial. There was a marked relative increase in delirium and psychosis, though not in any other psychiatric presentations. In preparation for further exponential rises in COVID-19 cases, we would expect seamless integration of liaison mental health teams in acute general hospital wards to optimise delirium management in patients with COVID-19. Further consideration should be given to adequate staffing of community and crisis mental health teams to safely manage the potentially increasing number of people reluctant to visit the emergency department.